White Psychologists and African Americans' Historical Trauma: Implications for Practice. Issue 4 (20th April 2016) - Danzer, Graham; Rieger, Sarah M.; Schubmehl, Sarah; Cort, Doug
ABSTRACT: This article reviews and synthesizes literature on the historical trauma of African Americans with an emphasis on how White psychologists can integrate awareness of historical trauma into clinical practice. Research supports that African Americans are affected by White racism in ways that parallel the effects of other interpersonal traumas. How African Americans are affected by racism depends on the individual, although the effects on the individual also occur within a shared cultural context. In addition to negative impacts, the literature also identifies African Americans' core strengths and coping strategies that have a similarly historical basis. These strengths and coping strategies are discussed in their implications for White psychologists' role in African Americans' trauma recovery process.